1999
DOI: 10.2527/1999.774840x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of direct, maternal, and grandmaternal genetic effects for weaning weight in several breeds of beef cattle.

Abstract: Weaning weights from nine parental breeds and three composites were analyzed to estimate variance due to grandmaternal genetic effects and to compare estimates for variance due to maternal genetic effects from two different models. Number of observations ranged from 794 to 3,465 per population. Number of animals in the pedigree file ranged from 1,244 to 4,326 per population. Two single-trait animal models were used to obtain estimates of covariance components by REML using an average information method. Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 26 publications
(40 reference statements)
8
33
0
2
Order By: Relevance
“…Any relationship of the estimates of the direct-grandmaternal correlation (r ag ), which ranged from −.36 to .37, with any of the other parameters was not obvious. Estimates with Model 5 generally agreed with previous studies in which a model with grandmaternal effects was applied (Dodenhoff et al, 1998(Dodenhoff et al, , 1999. Given a negative influence of the granddam's phenotype on the dam's maternal ability, Willham (1972) expected r mg to be negative, but he doubted that a nonzero covariance between direct and grandmaternal genetic effects existed.…”
Section: Estimation Of (Co)variance Componentssupporting
confidence: 71%
See 1 more Smart Citation
“…Any relationship of the estimates of the direct-grandmaternal correlation (r ag ), which ranged from −.36 to .37, with any of the other parameters was not obvious. Estimates with Model 5 generally agreed with previous studies in which a model with grandmaternal effects was applied (Dodenhoff et al, 1998(Dodenhoff et al, , 1999. Given a negative influence of the granddam's phenotype on the dam's maternal ability, Willham (1972) expected r mg to be negative, but he doubted that a nonzero covariance between direct and grandmaternal genetic effects existed.…”
Section: Estimation Of (Co)variance Componentssupporting
confidence: 71%
“…Dodenhoff et al (1999) used such a "grandmaternal" model to estimate genetic parameters in beef cattle. Model 5 in this study was the "grandmaternal" model (Willham, 1972):…”
Section: Methodsmentioning
confidence: 99%
“…The heritability of yolk T ( ) was high and 2 h p 0.75 comparable to the heritability of egg mass ( ) and 2 h p 0.84 yolk mass ( ) observed in our study as well as in 2 h p 0.97 other species (Christians 2002). This finding adds to the evidence for a genetic basis of prenatal maternal effects, which is well established for livestock (e.g., Meyer 1997;Dodenhoff et al 1999;Moce et al 2004) and plants (reviewed in Shaw and Byers 1998) but still scarce for freeliving animals. Yolk A4 deposition, on the other hand, was not heritable.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, Swalve (1993) suggested that the negative covariance between direct and maternal genetic effects may be the result of management system. However, an investigation conducted by Dodenhoff et al (1999) on several breeds of beef cattle indicates that dependences between direct and maternal effects are determined by breed. Moreover, showed that editing the database plays a role in estimating genetic parameters and includes a more complex pedigree as well as produces slightly different results.…”
Section: Resultsmentioning
confidence: 99%